Employee's Perception and Preferences Towards Implementing Biophilic Design in Workspace - Tan , Yeong En; Mohd Razif, Farhana (MAJ - Malaysia Architectural Journal, 2020)
Most of Malaysian spend one third of their time per day in an office workspace to be productive and contribute to their work or career. An office workspace should be designed to enhance productivity and creativity, by regulating or balance the mental and physical health of employee. The key to create such conducive working environment is through stress free, and restorative environment, which could be achieve through incorporate of biophilic design. This paper attempts to find out the current office environment and ways to achieve a stress-free office workspace environment through the implementation of biophilic design approach into office building. Also, to find out does building occupants appreciate or accept biophilic elements. Based on a review of literature of biophilic design, a checklist has been formed to find out the availability of biophilic element in KOMTAR. A Survey has been done to acquire user satisfaction of current workspace environment, along with perception and preference of biophilic design. The findings show that, the biophilic design approach is acceptable and viable generally. Building occupants had also chosen the choice given in the biophilic perception survey, that they wish to have biophilic elements and more nature connectivity in the workspace. Therefore, as an architect we should design a workspace there is more nature connected and ensure user experience a comfortable and healthy environment.